Collaborative optimization of rural residential land consolidation and urban construction land expansion: A case study of Huangpi in Wuhan, China. (March 2019) - He, Qingsong; Tan, Shukui; Yin, Chaohui; Zhou, Min
Abstract: The synergetic development of urban and rural construction land is always an important issue. We propose a collaborative optimization model (COMRU) of rural residential land consolidation and urban construction land expansion, which is a coupling model of cellular automata (CA), genetic algorithms (GA), and the Lewis turning point theory. This model regards the rural population transfer as a scenario and generates a new quantity and space allocation system for the population and the land-use types in the study area. The optimized result will balance the development of urban and rural construction lands to ultimately reduce the income gap between urban and rural areas and promote the rationality of the spatial distribution of urban and rural construction lands. We applied COMRU to Huangpi District in the city of Wuhan, the capital of Hubei Province, People's Republic of China and obtained three important results: (1) After optimization, the scattered rural settlements were effectively consolidated and large amounts of land resources were released, thereby supplementing cultivated and urban construction lands; (2) The urban–rural income ratio decreased significantly, indicating a considerable reduction in the income gap between the urban and rural areas; (3) The structure and function of the construction lands were improved, leading to the improved equity of urban and rural public services. The final space optimization allocation program generated by COMRU provides a reference for the sequence of rural settlement consolidation and urban spatial planning. Highlights: We proposed a collaborative optimization model for rural-urban Land allocation. Rural population flow was the model scenario when building the model. The simulation results make each land use quantitatively and spatially optimized. Optimized allocation result provides a reference for consolidating the rural settlements.